Corrosion in orthodontic mini-implants: a literature review - Laquihuanaco Coarita, Gina Maritza (2022)
Mini-implants are metallic devices that are temporarily fixed to the bone and are used to achieve a wide variety of orthodontic movements. Today, they have become an important device that helps the orthodontist in all stages of treatment. The mini-implants are made with joints of different metals, so they are exposed to the corrosion process in the oral cavity. The release of ions can cause adverse physiological effects, including cytotoxicity, genotoxicity, carcinogenicity, and allergenic effects. This article seeks to review the corrosion of orthodontic mini-implants. The literature reports that the corrosion of mini-implants contributes to inflammation, which is a factor that influences the loss of these devices and the release of metal ions is one of its main causes. Additionally, corrosion can produce perforations and loss of thickness of the metal, which reduces the mechanical resistance and increases the risk of fracture.